PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA SENTOSA MOTOR - Ni Wayan Desi Suryanti; Nengah Sukendri (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The purpose of this study is to examine how Sentosa Motor customers’ purchasing decisions are influenced by pricing and service quality. This is a result of intense competition in the automobile industry, particularly in motorcycle repair and spare parts sales. The factors that influence customer choices are critical to the company’s survival.Methods: One hundred individuals who have made purchases at Sentosa Motor were given questionnaires as part of this study’s quantitative methodology. Multiple linear regression was used to evaluate the data, and t-tests, F-tests, reliability and validity tests, and traditional assumption tests were used to make sure the model was valid.Results: The findings demonstrate that service quality significantly and favorably influences purchasing decisions, while price has no effect. Despite both factors having a significant impact on purchase decisions, the coefficient of determination indicates their contribution is negligible. These results suggest that when consumers make decisions, service is more important than price. The study’s findings indicate that Sentosa Motor needs to keep enhancing service quality and take into account more aggressive pricing tactics in order to boost customer attraction and loyalty. Keywords: Consumers, Price, Purchasing Decisions, Service Quality,